Enhancement of methane production from palm oil mill effluent through co-digestion and bio-augmentation treatment - Mohd Yaakob, Nurliyana (2016)
Degradation process of palm oil mill effluent (POME) via anaerobic digestion produced a valuable methane gas which has recently become a potential source of renewable energy in Malaysia. As to date, only a few palm oil mills in Malaysia are involved in recovering the biogas since current methane production by conventional technologies is below expectation. The composition of POME exhibits nutrient availability for the indigenous microorganisms and will affect the direction of the degradation process. Similarly, the performance of microbial community during the treatment process plays a significant role as they are primarily the agents that accomplish the desired treatment. This research aims at assessing the effects of POME characteristics on the methane production and subsequently investigating ways of enhancing the methane productivity by improving the feedstock characteristics and microbial consortia. This study was divided into three parts. The first part evaluates the POME physicochemical and biochemical characteristics. Total carbon of POME was found to be relatively low leading to low carbon to nitrogen (C/N) ratio value which affects the production of methane gas. In addition, a low pH value of POME was recorded, influencing the optimum condition of indigenous microbes specifically the methanogens during the digestion process. The second and third part of this study were conducted to improve the feedstock characteristics as well as to increase the methane productivity and substrate degradability by conducting the co-digestion and bioaugmentation treatment.Co-digestion treatment of POME with natural carbon substrate in the palm oil mill, specifically empty fruit bunch (EFB), was investigated by varying the C/N ratio of the substrates loading. A significant effect of different C/N ratios towards methane production and methane yield were observed. The co-digestion treatment resulted in higher methane production where C/N ratio of 45 delivers the highest result with twelve times and 61.7% improvement in methane production and methane field, respectively. While for substrate biodegradability,a significant reduction of organic substances was identified with different C/N ratios except for degradation of cellulose content in EFB. However, co-digestion samples were found to be ineffective in terms of substrate degradability compared to mono-digestion of POME in total reduction of total solid (TS), biological oxygen demand (BOD) and chemical oxygen demand (COD) respectively for POME substrate. While in EFB substrate degradability, a low total reduction was observed for all co-digestion samples. Cellulose content particularly indicates an increase in percentage after the digestion process. Bioaugmentation treatment towards POME and POME co-digested with EFB was investigated by addition of different microbial loadings of cellulolytic bacteria and methanogenic archaea by single or co-augmentation technique, to improve the microbial activity in the feedstock and to enhance the methane productivity and substrate biodegradability. Treatment of single augmentation by Bacillus subtilis in co-digestion sample at 10% microbial loading (C-B10) resulted in the highest methane production with 14.3% increment compared to non-augmented co-digestion sample. In the matter of substrate degradability, bioaugmentation treatment of C-B10 activated the cellulose reduction in EFB with 1.95% reduction as compared to non-augmented co-digestion sample which had an increased value of 4.4%. Besides, sample C-B10 recorded better TS, total volatile solid (TVS), COD, organic matter (OM) and lignin reduction with 27.2%, 22.3%, 90.9% 29.4% and 2.8 times higher degradation, respectively compared to the non-augmented co-digestion sample.Treatment of co-augmentation between B. subtilis and mix methanogens was operated to maximize the methane productivity and substrate degradability. Sample of single digestion co-augmented at 5% microbial loading (S-B5-M5) gives a significant increase in methane productivity with 9.4-29.6% and relatively 2.1 times improvement compared to single augmented sample of similar microbial loading (S-B5 and S-M5) and the non-augmented single digestion sample respectively. In terms of substrate degradability, sample of S-B5-M5 showed a notable results in TVS and COD reduction where it attained the highest removal efficiencies among all co-augmented samples with 37.3% and 55.2% improvement measure up to non-augmented single digestion sample. Co-digestion and bioaugmentation treatment were demonstrated as effective means of enhancing the methane productivity and substrate biodegradability of the feedstock. Optimum loading of the co-substrate and microbial cultures from this research can be implemented in the field to better develop the methane production system specifically in the closed anaerobic pond. A substantial number of palm oil millers will be able to apply the results of this study and broaden the chances to recover the biogas produced into a valuable renewable energy.